Study on the Association of Dietary Fatty Acid Intake and Serum Lipid Profiles With Cognition in Aged Subjects With Type 2 Diabetes Mellitus - Li, Pengfei; Gao, Yanyan; Ma, Xiaojun; Zhou, Shaobo; Guo, Yujie; Xu, Jingjing; Wang, Xixiang; Van Halm-Lutterodt, Nicholas; Yuan, Linhong (Frontiers in Aging Neuroscience, 2022)
Background: The correlation between dietary fatty acids (FAs) or serum lipid with cognition in aging population has been reported by previous study. However, the association of dietary FAs and serum lipid profile with cognition in subjects with type 2 diabetes mellitus (T2DM) is seldom reported. Objectives: A cross-sectional study was conducted to explore the correlation of dietary FAs intake and serum lipid profiles with cognition in aging Chinese with T2DM. Methods: 1526 aging Chinese subjects were recruited from communities. Fasting blood samples were collected for parameter measurement. Food frequency questionnaire (FFQ) method was applied for dietary survey. Cognition was assessed by Montreal Cognitive Assessment (MoCA) test. Dietary FAs intake and serum lipid levels were compared between T2DM and control subjects. Logistic regression was applied for analyzing the association of FAs intake, serum lipid levels with the risk of mild cognitive impairment (MCI) in T2DM and control subjects. Results: The T2DM and control groups showed significant difference in serum lipid levels. Results of logistic regression analysis demonstrated the potential associations of serum TC, LDL-c, dietary n-3 PUFAs intake with the risk of MCI in T2DM subjects, but the associations were not observed in control subjects. Conclusions: The T2DM phenotype might affect the relationship between dietary FAs intake, circulating lipids and cognitive performance. Large prospective cohort studies are needed to uncover the underlying mechanism of how diet FAs intake, serum lipids affecting cognition in T2DM aging subjects.